PENGARUH KESENJANGAN DIRI DAN SIKAP TERHADAP UANG PADA PERILAKU PEMBELIAN KOMPULSIF - Nur Pratiwi; Narto Irawan Otoluwa (POINT: Jurnal Ekonomi dan Manajemen, 2019)
This research is determine to find effect of self-discrepancy and money attitude toward the tendency of compulsive buying It was included 220 Indonesian consumer as respondent by using questionnaire to collect data from the respondent at least we reach 213 valid questionnaire that can be used in this research. The multiple regression was used as an anlytical tool in attempt to determine the direct effect between self-discrepancy and money attitude toward compulsive buying tendency.Self discrepancy proved doesn't have significant effect toward compulsive buying tendency as with the power prestige dimension of sikap terhadap uang. But distrust dimension otherwise have had positive and significant effect toward compulsive buying tendency which is totally different with the previous study which found negative and significant effect. And for the anxiety dimension of sikap terhadap uang found to be positive and significant toward compulsive buying tendency.